Legal Perspectives of Public Debt Management in South Eastern Europe - Aleksandar Stojkov; Aleksandra Maksimovska (Institut für Ostrecht, Munich, Germany, 2015)
This study examines the legal and institutional underpinning of public debt management in six South Eastern European transition countries and highlights the short- and medium-term challenges for law- and policymakers. The more specific research goals of the study are: (1) to contrast and compare the structure of legal frameworks for public debt management in the SEE countries, (2) to assess the important factors for developing a sound institutional structure for an effective debt management, and (3) to offer policy relevant conclusions for the observed countries. The study contributes to the existing body of relevant literature in several ways. To the best of our knowledge, this is the first attempt to provide a comprehensive analysis of the institutional arrangements influencing the prudent public debt management in the region of South East Europe. The second intended contribution of the paper is to highlight the main challenges for efficient, transparent and accountable debt management policies in these countries. Due to the low political culture in many SEE countries, the legal provisions relating to the fiscal transparency in the debt management law must be much more detailed and explicitly stated. Several areas of fiscal transparency call for urgent action. The deficiencies can be detected in many areas starting from the definitional point of view (e.g., the coverage of the officially published general government and public debt) to legal ambiguities to the extraordinary (ad hoc) issuance of government securities to problematic quality and timeliness of the debt reports to the lack of audit of the public debt.